Spirituality in Occupational Therapy Practice According to New Graduates. (October 2019) - Misiorek, Anna; Janus, Edyta
Occupational therapy practitioners consider spirituality to be significant in affecting the process and outcome of occupational therapy; however, many therapists voice confusion and concern about its application within their practice. This study aimed to describe the personal definition of spirituality of young occupational therapy practitioners and their perspectives on its application to their practice. Thirty-five young occupational therapists, engaged in a postprofessional master's degree, were interviewed using a self-prepared questionnaire, which included open and close-ended questions. The data was analysed using qualitative and quantitative methods. Most participants defined spirituality as a driving force, which shapes many aspects of life. More than half of the participants considered spirituality as crucial in forming therapeutic relationships. The findings suggest that inclusion of spirituality within occupational therapy education warrants further research.